Enhancing Zakat Governance: Implementation of the SIMBA System Across BAZNAS Levels - Riyanto, Dwi; Fakkanna, Mukhaer (Center of Strategic Studies (PUSKAS) BAZNAS, 2024)
The development of technology has had a major impact on the management of zakat in Indonesia, particularly through the use of management information systems by the National Agency for Amil Zakat (BAZNAS). In order to simplify zakat management and increase transparency, BAZNAS developed a management information system called SIMBA. Although many previous studies discuss SIMBA, most of them focus only on the regional level and thus do not provide a comprehensive picture of its national implementation. This research aims to provide a comprehensive overview of the implementation of SIMBA at the provincial, district and city levels and to identify supporting and inhibiting factors in an effort to improve the use of SIMBA to optimise zakat management in Indonesia. This research uses a qualitative approach and a case study methodology to analyse the implementation of SIMBA at different levels of BAZNAS across Indonesia in order to provide a comprehensive picture of the use of SIMBA application in Indonesia.